EVALUATION OF MORPHOBIOLOGICAL CHARACTERISTICS AND TOLERANCE TO RUST DISEASES OF WINTER BREAD WHEAT (Proceedings of International Educators Conference, 2024)
The selection of starting materials is the main factor in the creation and production of productive bread wheat varieties resistant to rust diseases for the irrigated areas of our republic. In this case, the main task of the breeders is to transfer the best lines to the next stages according to the features of disease resistance and morpho-biological characteristics of the lines created by hybridization methods.